Prevalence and Clinicomycological studies of Otomycosis: A review - Nipa, KK; Kamal, AHM; Imtiaj, A (Journal of Bio-Science, 2019)
Otomycosis is a chronic ear disease of external auditory canal and it is more prevalent in warm, humid and dusty environment, although it is now found throughout the world. The most commonly found causative agents as of fungal species are Aspergillus and Candida along with preponderance of various fungal and bacterial species has also been reported. The aim of this review is to focus on the prevalence of causal agents of otomycosis in the global context and its clinical management. A total of 63 research articles have been reviewed, which deals prevalence of otomycosis. Its clinicomycological studies both separately and altogether with folk medicine in relation to treatment of otomycosis were also reviewed. Findings of various reports revealed that the Aspergillus and Candida species are the main causal agents of otomycosis. But many reports indicate that a few of other fungal species along with bacteria particularly Staplylococcus aureus and Pseudomonas aeruginosa are also responsible for accelerating this disease in human all over the world. In many reports, improper self-cleaning of ear has been found as major predisposing factor of otomycosis. This review suggests that health education, improvement of socioeconomic status and health caring facilities should be increased for reducing prevalence of otomycosis. However, more research needs to be carried out because of its severe parallel effects to the human health. J. bio-sci. 28: 121-135, 2020